In vitro Evaluation of the Safety of Adalimumab for the Eye Under HTLV-1 Infection Status: A Preliminary Study - Kurozumi-Karube, Hisako; Kamoi, Koju; Ando, Naoko; Uchida, Minami; Hamaguchi, Isao; Ohno-Matsui, Kyoko (Frontiers in Microbiology, 2020)
Adalimumab, a fully human monoclonal tumor necrosis factor (TNF)-α antibody, is one of the most widely used biologics in the treatment of inflammatory diseases. However, adalimumab can exacerbate infectious conditions, induce paradoxical reactions such as inflammation, and cause neoplasia. Human T-cell leukemia virus type 1 (HTLV-1) is an infectious agent that induces inflammation and neoplastic infiltration in the eye. To date, numerous HTLV-1 carriers have been treated with adalimumab to suppress inflammation out of necessity, when standard anti-inflammatory drugs such as steroids and immunosuppressive agents have proven inadequate to control the inflammation. Here, we clarify the safety of adalimumab for the eye under HTLV-1 infectious conditions in vitro. We used the ARPE-19 cell line as ocular resident cells, and used MT2 and TL-Om1 as HTLV-1-infected cells. ARPE-19 and MT2/TL-Om1 were co-cultured, then adalimumab was administered. Production of cytokines and chemokines, TNF- receptor (TNF-R), HTLV-1 proviral load (PVL), and apoptosis were measured to assess the effects of adalimumab. Contact between ARPE-19 and MT2/TL-Om1 produced inflammatory cytokines such as TNF, interleukin (IL)-6, IL-8 and IL-10, and transduced chemokines such as interferon-inducible protein-10, monocyte chemotactic protein-1, monokine induced by interferon-, and regulated on activation, normal T cell expressed and secreted. No inflammatory cytokines and chemokines were exacerbated by adalimumab. Expression of TNF-R on ARPE-19 and MT2/TL-Om1 cells, HTLV-1 PVLs of MT2/TL-Om1 cells, and cell growth rate and apoptotic rate of ARPE-19 were unaffected by adalimumab. In conclusion, adalimumab does not appear to exacerbate HTLV-1-associated inflammatory conditions in the eye or increase PVL in HTLV-1-infected T cells. These data suggest that adalimumab could be used safely for the eye under HTLV-1 infectious conditions from the perspective of in vitro assessment.